2020
DOI: 10.1111/nph.16670
|View full text |Cite
|
Sign up to set email alerts
|

OsPP2C09, a negative regulatory factor in abscisic acid signalling, plays an essential role in balancing plant growth and drought tolerance in rice

Abstract: Summary Plants maintain a dynamic balance between plant growth and stress tolerance to optimise their fitness and ensure survival. Here, we investigated the roles of a clade A type 2C protein phosphatase (PP2C)‐encoding gene, OsPP2C09, in regulating the trade‐off between plant growth and drought tolerance in rice (Oryza sativa L.). The OsPP2C09 protein interacted with the core components of abscisic acid (ABA) signalling and showed PP2C phosphatase activity in vitro. OsPP2C09 positively affected plant growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…Plants cope with drought stress by regulating phytohormones (such as abscisic acid [ABA], jasmonic acid [JA], and auxin) or making osmotic adjustments [8]. These mechanisms of drought stress response involve genes belonging to various families including WRKY, MYB, NAC, ABRE, PP2C, and SnRK2 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Plants cope with drought stress by regulating phytohormones (such as abscisic acid [ABA], jasmonic acid [JA], and auxin) or making osmotic adjustments [8]. These mechanisms of drought stress response involve genes belonging to various families including WRKY, MYB, NAC, ABRE, PP2C, and SnRK2 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As we demonstrated that the OsRF1 targets a key repressor of ABA signaling OsPP2C09 ( Figures 6A,B ) and as previous reports indicated that the phosphorylation status was closely correlated with the protein stability of DELLA proteins ( Wang et al, 2009 ; Dai and Xue, 2010 ; Qin et al, 2014 ; Blanco-Tourinan et al, 2020 ), we further investigated the SRL1 protein level in the OsPP2C09-OE transgenic rice. The OsPP2C09 -OE transgenic rice was reported to display hypersensitive phenotypes in response to ABA, drought, and salinity ( Miao et al, 2020 ; Min et al, 2021 ). Interestingly, Figure 7C clearly indicates that the SLR1 protein level was much lower in the OsPP2C09 -OE transgenic rice than in the WT plants in the presence of 5 μM GA 3 or 50 μM ABA.…”
Section: Resultsmentioning
confidence: 99%
“…OsRF1 could participate in the regulation of ABA signaling and stress responses by controlling the OsPP2C09 protein dynamics under stress conditions. Recently, it was reported that overexpression of OsPP2C09 displayed ABA-insensitive and stress-hypersensitive phenotypes, and that the knock-out mutant of OsPP2C09 showed enhanced stress tolerance and ABA hypersensitivity ( Miao et al, 2020 ; Min et al, 2021 ). Although the OsPP2C09 protein level is known to be regulated by the 26S proteasome pathway ( Miao et al, 2020 ), the mechanism of PP2CA09 degradation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, all GmPYLs , GmPP2Cs , and GmSnRK2s genes contain at least one plant hormone response element, and plant hormone signals are the key to regulating drought or water deficiency responses [ 52 ]. Therefore, GmPYL-PP2C-SnRK2s gene families may play an important role in regulating drought or water deficiency responses [ 53 ].…”
Section: Discussionmentioning
confidence: 99%